The origin of the mineralizing fluids in different type mineralizations associated with the Upper Cretaceous Elazig Magmatic Complex, Turkey; an isotopic approach - Akgul, Muharrem (Pergamon-Elsevier Science Ltd, 2016)
This study examined the origin and properties of mineralized fluids by using C, O and S isotopes in different type mineralizations associated with the Upper Cretaceous Elazig Magmatic Complex. The isotopic compositions of vein type mineralizations show that the thrust zone affects the formation of the Karakas iron mineralization by meteoric and magmatic hydrothermal solution mixtures due to the average delta O-18(H2O) value 6.40 parts per thousand. The calculated delta O-18(H2O) composition values is 5.20 parts per thousand in biotite from the Kizildag vein type Cu-Pb-Zn mineralizations, which is consistent with a magmatic origin of the fluids. The calculated delta O-18(H2O) composition is 4.30 parts per thousand that indicates a medium and low temperature magmatic hydrothermal fluid effect. The skarn type mineralizations isotopic compositions indicate that the calculated delta C-13(CO2) values are between -12.70 parts per thousand and -36.39 parts per thousand that could be late magmatic fluids that were modified by interaction with the host meta-sedimentary rocks and with meteoric water at the Birvan and Asvan iron mineralizations. Also the delta O-18(H2O) values in quartz of the Meseli iron mineralization are between 0.70 parts per thousand and 1.30 parts per thousand. The lower delta O-18(H2O) oxygen isotope composition compared to magmatic origins must be hydrothermal solutions mixing with meteoric waters. In the massive sulfide type Kavalli and Derince pyrite samples, delta S-34(H2S) values are between 17.73 parts per thousand and 20.63 parts per thousand. These values clearly indicate the volcano-sedimentary effect on hydrothermal solutions, which form the mineralization. The first findings of this study present information that all of the measured isotopic composition was modified by mixing metamorphic, magmatic and meteoric waters in the final stages of the hydrothermal solutions circulation. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Elazig Magmatic Complex; Eastern Taurid; Mineralization; Stable isotopes; Turkey